Bryozoa on disarticulated bivalve shells from Todos os Santos Bay, northeastern Brazil, with the description of two new species - Almeida, Ana C.s.; Souza, Facelucia B.c.; Farias, Jamile; Alves, Orane F.s.; Vieira, Leandro M. (Zootaxa, 2018)
As sessile organisms, bryozoans are among the commonest components of the encrusting communities on hard substrata. On unconsolidated bottoms, benthic animals and their carapaces, including mollusk shells, represent potential surfaces for encrustation. Here we describe the bryozoan fauna growing on disarticulated bivalve shells collected intertidally on Itaparica beach, Todos os Santos Bay, northeast Brazil. We examined a total of 382 valves representing seven species of bivalves, among which we found 82 valves of three bivalve species to be encrusted by bryozoans, with 109 bryozoan colonies detected overall. We identified 11 cheilostome bryozoan species, among which Phidoloporidae and Smittinidae were the most diverse, with four and two species, respectively. We redescribed two bryozoan species, Parasmittina loxoides and Rhynchozoon phrynoglossum, and describe another two, Pleurocodonellina marcusi n. sp. and Rhynchozoon itaparicaensis n. sp., as new. A new combination for Cribella triangulata Canu & Bassler, 1928 is proposed, including Calyptotheca tenuata Harmer, 1957 as a new junior subjective synonym of Calyptotheca triangulata n. comb. All but one of the 11 species have encrusting colonies; Licornia aff. diadema, forms erect branching colonies. For seven of the bryozoans, ours are the first records of these species growing on shells. Although the majority of bryozoans we studied have also been reported on other substrata, Rhynchozoon brasiliensis and Parasmittina loxoides were predominant in the fauna, comprising 79 (72%) of all colonies inventoried. Due to the lack of information on the distribution of these species in northeastern Brazil, further studies are needed to determine whether they show any substratum preference.